Estimation of tumour mass in patients with differentiated thyroid carcinoma using serum thyroglobulin - Rosenbaum-Krumme, S. J.; Wieduwilt, M.; Nagarajah, J.; Bockisch, A.; Jentzen, W. (Nuklearmedizin - NuclearMedicine, 2012)
Serum thyroglobulin (Tg) is a reliable tumour marker in follow-up of patients with differentiated thyroid carcinoma (DTC). A positive correlation between Tg level and tumour mass was recently observed, but no attempts were made to derive a numerical relation. The aim of this study was to derive a numerical relationship between serum Tg level and tumour mass that allows optimizing the diagnostic procedures. Patients, method: 78 DTC patients with tumour lesions in either 124I-NaI or 18F-FDG PET/CT were included. For each patient, the total tumour mass was determined functionally in iodine- and FDG-positive lesions as well as morphologically in only CTpositive lesions. The serum Tg level was measured under TSH stimulation prior to imaging. Regression analyses were performed to derive an approach for estimation of the total tumour mass based on Tg levels. Results: A positive correlation of serum Tg and tumour mass was confirmed and a mathematical expression was given to estimate the tumour mass along with its 95% confidence interval using only the serum Tg level. The results demonstrated that the range of predicted tumour mass was higher per serum Tg unit for iodinepositive lesions than for FDG-positive tumour lesions and was higher for follicular than for papillary thyroid carcinoma. Conclusion: This study provides an approach to estimate the tumour mass and its 95% confidence intervals in DTC patients using the serum Tg level. The range of the estimated tumour mass for a given Tg level is rather large, and therefore, the approach is of limited value in clinical application.
Keywords: Thyroid carcinoma; thyroglobulin; tumour mass; correlation